Kebijakan Pembaruan Hukum Pidana Tentang Pidana Kerja Sosial Dalam KUHP Nasional : Perspektif Tujuan Pemidanaan - Wicaksana, Villar Wibawa; Mas Putra Zenno Januarsyah (JURNAL USM LAW REVIEW, 2025)
The research aims to analyze the concept of social work punishment based on the National Criminal Code (KUHP) and formulate an ideal model for its implementation from the perspective of criminal law reform policy. The research background originates from the conditions of correctional institutions experiencing overcrowding and over-capacity, coupled with negative societal stigmatization towards convicts, which demonstrates the continued dominance of an absolute and retributive punishment paradigm. The research urgency lies in the necessity of an in-depth study of social work punishment as one of the new legal instruments in the National Criminal Code that prioritizes restorative and rehabilitative values. The research methodology employs a normative juridical approach with descriptive specifications, conducted through a literature study and qualitative analysis of primary, secondary, and tertiary legal materials. The research novelty focuses on a comprehensive examination of social work punishment within the context of Indonesian criminal law reform. The research findings indicate that social work punishment in the National Criminal Code represents a penalization aimed at restorative and rehabilitative objectives, signifying a paradigm shift in punishment goals, with its ideal implementation model being a product of criminal legal politics that utilizes a rational approach to achieve social order and community welfare in accordance with the procedural mechanism outlined in Article 85 of the National Criminal Code.   Tujuan penelitian ini adalah menganalisis konsep pidana kerja sosial berdasarkan KUHP Nasional dan merumuskan model ideal penerapannya dalam perspektif kebijakan pembaruan hukum pidana. Latar belakang penelitian bermula dari kondisi lembaga pemasyarakatan yang mengalami overcrowding dan overcapacity, serta stigmatisasi negatif masyarakat terhadap terpidana, yang menunjukkan masih dominannya paradigma pemidanaan bersifat absolut dan sekadar pembalasan. Urgensi penelitian terletak pada perlunya kajian mendalam tentang pidana kerja sosial sebagai salah satu instrumen hukum baru dalam KUHP Nasional yang mengedepankan nilai restoratif dan rehabilitatif. Metode penelitian menggunakan pendekatan yuridis normatif dengan spesifikasi deskriptif, melalui studi kepustakaan dan analisis kualitatif terhadap bahan hukum primer, sekunder, dan tersier. Kebaharuan penelitian fokus pada kajian komprehensif pidana kerja sosial dalam konteks pembaruan hukum pidana Indonesia. Hasil penelitian menunjukkan bahwa pidana kerja sosial dalam KUHP Nasional merupakan pemidanaan bertujuan restoratif dan rehabilitatif, yang menandakan pergeseran paradigma tujuan pemidanaan, dengan model ideal penerapannya merupakan produk politik hukum pidana yang menggunakan pendekatan rasional untuk mencapai ketertiban dan kesejahteraan masyarakat sesuai mekanisme prosedural Pasal 85 KUHP Nasional.